Development and effectiveness of a mobile health-based nutrition education intervention on maternal, infant and young child nutrition to prevent stunting in Kelantan: a study protocol - Norshafawati Abd Azimi; Bibi Nabihah Abdul Hakim; Hamid Jan Jan Mohamed; Tengku Alina Tengku Ismail; Hafzan Yusoff; ZAMH Zabidi-Hussin; Yee Cheng Kueh; Surianti Sukeri; Puspawati Mohamad (Universiti Putra Malaysia, 2024)
Introduction: The first “1000 days” is a critical period of opportunity for interventions to prevent stunting and other health problems. This paper describes a study protocol of a mobile phone-based nutrition education (MiNd) intervention on maternal, infant and young child nutrition. Methods: This is a six-months quasi-experimental intervention consisting of three phases; (i) Phase 1 - development of MiNd intervention modules, (ii) Phase 2 - evaluation of the effectiveness of MiNd intervention, and (iii) Phase 3 - a qualitative study exploring perceptions and experiences of the intervention. Discussion: Assessment of anthropometry, dietary intake, food security, mental health, knowledge, attitude, and practice (KAP) of food intake during pregnancy and breastfeeding will be evaluated during pre and post intervention. This is the first comprehensive mobile phone-based nutrition intervention study on pregnancy, lactation, and infant growth in Malaysia. The findings will be useful in modulating health intervention programme to prevent stunting and other health issues nationwide. Trial registration: NCT04606706.